Didactic transposition as a field in the arithmetic-algebra transition: A systematic review - García-Fajardo, Victoria Alejandra (2026)
Objective. To analyze the academic production related to the transition from arithmetic to algebra in primary and secondary schools from the perspective of didactic transposition. Methodology. To achieve this objective, a systematic literature mapping was developed to obtain a structured overview of the academic production related to the object of study. The search was conducted in Scopus, Web of Science, and ScienceDirect, considering the period 2014–2024. Inclusion and exclusion criteria were applied, and qualitative techniques such as coding and thematic categorization were used. The documents were systematized using a Structured Analysis Grid (SAG) for subsequent synthesis and interpretation. Results. A diversity of pedagogical and didactic approaches aimed at facilitating the transition from arithmetic to algebra through didactic transposition was identified. However, a significant gap was evident in the conceptualization of didactic transposition as a structured field of power relations, knowledge, and discourse within the educational sphere. Discussion and conclusions. Recognizing didactic transposition as a field allows us to understand how teaching discourses and practices shape educational dynamics in different contexts. This approach broadens our understanding of educational transitions and opens lines of research focused on the critical analysis of pedagogical practices and teacher training.